2014
DOI: 10.1074/jbc.m114.586461
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Protein Induces Urokinase-type Plasminogen Activator (uPA) by Forming a Complex with NF-κB p65 Transcription Factor and Binding to the uPA Promoter, Leading to Enhanced Invasiveness of Cancer Cells

Abstract: Background: Molecular mechanism by which MUC1 promotes cancer cell invasion is unclear. Results: MUC1 forms a complex with NF-B p65 transcription factor and binds to urokinase-type plasminogen activator (uPA) promoter, and thereby induces uPA expression. Conclusion: uPA induced by MUC1 promotes cancer cell invasion. Significance: uPA is a useful target for inhibiting invasion by MUC1-expressing cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 52 publications
5
27
0
Order By: Relevance
“…MUC1 suppresses activation of the ARF-MDM2-p53 pathway (39). In MUC1-expressing cells, a MUC1 co-operating NF-κB signaling pathway plays a critical role in cancer cell invasion (40). MUC1 deficiency impairs NFKB p65, Akt and MAPK pathways, which indicated that MUC1 appears to be a good therapeutic target to slow down esophageal tumor progression (41).…”
Section: Discussionmentioning
confidence: 99%
“…MUC1 suppresses activation of the ARF-MDM2-p53 pathway (39). In MUC1-expressing cells, a MUC1 co-operating NF-κB signaling pathway plays a critical role in cancer cell invasion (40). MUC1 deficiency impairs NFKB p65, Akt and MAPK pathways, which indicated that MUC1 appears to be a good therapeutic target to slow down esophageal tumor progression (41).…”
Section: Discussionmentioning
confidence: 99%
“…Human MUC1 gene transfectants (HCT116/MUC1 and A549/ MUC1) and the respective control cells (HCT116/Mock and A549/Mock) were prepared as described previously (34). Human MUC1 gene knockdown cells (SKOV3/Si-1 and -2) and MUC1-expressing cells (SKOV3/Scr) were generated as described previously (35). Human galectin-3 gene knockdown HCT116/MUC1 cells (HCT116/MUC1-Gal-3/Si) and control cells (HCT116/MUC1-Scr) were generated by introducing human galectin-3 shRNA and scrambled shRNA vectors (InvivoGen, San Diego, CA), respectively, into HCT116/MUC1 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of Total RNA and DNA Microarray AnalysisPreparation of total RNA and DNA microarray analysis were performed as described previously (35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicated the potential role of this molecule in the occurrence and progression of prostate cancer. Limited information is available on the association between HOTAIR and MUC1; however, other studies have reported on the involvement of the links of HOTAIR and MUC1 to NF-κB were found in oncogenic signaling pathways and tumor progression [34,35].…”
Section: Introductionmentioning
confidence: 99%